Association between Patient’s Educational Degree with Level of Knowledge and Perception Regarding Pulmonary Tuberculosis (Medico Legal Update, 2021)
Background: Indonesia is the second largest population of pulmonary tuberculosis (TB) worldwide.Unfortunately, this condition has remained unchanged past decade. Education is essential for the formationof knowledge and perception, which is important, due to its impact on tuberculosis treatment implementation.Objective: The aim of this study is to determine the association between patient’s educational degree withknowledge and perception regarding pulmonary tuberculosis.Method: This was observational analytic study with cross-sectional design. The study was conducted on 51patients in TB outpatient clinic from Siti Khodijah Hospital and two Primary Health Care in Sidoarjo. Usingsimple random sampling, a questionnaire was formed to obtain related information about the variablesstudied; including baseline characteristic (age, gender, education, occupation), patient’s knowledge,and perception regarding pulmonary tuberculosis. Then parameter’s of knowledge and perception wereclassified: good and low.Results: Using multivariate analysis of Wilcoxon test, there was a significant difference between each groupof patient educational degree with knowledge regarding tuberculosis (p = 0.00) and perception regardingtuberculosis (p = 0.00).Conclusion: Different patient educational degree shows different knowledge and perception regardingPulmonary TB. This result may indicate that the educational degree affected the patient to understand thedisease. The collaborative approach needed to build proper patient’s knowledge and perception. Lack ofknowledge regarding TB, may due to a deficiency in Indonesian school curriculum content. These resultswill inform the development of relevant education, and information system, to enhance awareness abouttuberculosis in society.